2020
DOI: 10.3389/fvets.2020.00229
|View full text |Cite
|
Sign up to set email alerts
|

Epitheliotropic Infections in Wildlife Ruminants From the Central Alps and Stelvio National Park

Abstract: The mountain chain of the Alps, represents the habitat of alpine fauna where the red deer (Cervus elaphus) population is the outmost numerous, followed by the chamois (Rupicapra rupicapra) and the alpine ibex (Capra ibex) at higher altitudes. Previous reports showed the circulation of epitheliotropic viruses, belonging to the families Papillomaviridae and Poxviridae, causing skin and mucosal lesions in wild ruminants of the Stelvio National Park, situated in the area. To deepen our knowledge on the natural dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 60 publications
2
10
0
Order By: Relevance
“…The PV DNA was detected in the tissue samples of fibropapillomas in all seven cases using PCR. The neoplastic lesion size and numbers, as well as the gross pathology and histopathology of the neoplastic lesions observed in this study, were consistent with previous studies of roe deer and red deer cutaneous fibropapillomatosis [14][15][16][17]22,34]. Thus, it can be assumed that the firm, round, usually hairless and pigmented, eroded or ulcerated lesions located in almost all body parts are characteristic for cutaneous fibropapillomatosis associated with the CcaPV1 infections in roe deer.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The PV DNA was detected in the tissue samples of fibropapillomas in all seven cases using PCR. The neoplastic lesion size and numbers, as well as the gross pathology and histopathology of the neoplastic lesions observed in this study, were consistent with previous studies of roe deer and red deer cutaneous fibropapillomatosis [14][15][16][17]22,34]. Thus, it can be assumed that the firm, round, usually hairless and pigmented, eroded or ulcerated lesions located in almost all body parts are characteristic for cutaneous fibropapillomatosis associated with the CcaPV1 infections in roe deer.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, very low variability between the CcaPV1-type genomes (99.95% identity at the complete genome level compared to the sequences deposited in GenBank) and the CePV1v-type variant genomes (99.96-99.99% identity at the complete genome level compared to the sequences deposited in GenBank) was observed, with five out of six CcaPV1 genomes being 100% identical. Similar results were observed by Gallina et al [22], who reported two complete CePV1v genomes that were 100% identical. This observation is in agreement with the generally accepted evolutionary mechanism of PVs, which present a very slow mutation rate.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Despite the benign characteristics of the lesions, in some cases, bovine papillomatosis can dramatically reduce production performance when lesions are spread throughout the body, involving teats and udders. We have previously shown that the so-called “papillomatosis” can be the result of multiple infections with epitheliotropic viruses, including zoonotic poxviruses [ 1 , 2 ].…”
mentioning
confidence: 99%